The Effect of Company Size, Investment Decisions and Capital Structure on Company Value of Mining Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period - Andry; Menhard (Indonesian Journal of Banking and Financial Technology, 2023)
This study aims to find out what effect company size, investment decisions and capital structure have on company value in Mining Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample for this research is 33 companies x 5 years of financial statements so that the total sample is 165. The technical data used is multiple linear regression using SPPS 21. The results of the tests conducted show that the coefficient of determination (Adjusted R Square) is 0.304 or 30.4% this means that 30.4% of the variable company value can be explained or influenced by the variable company size, investment decisions and capital structure in mining companies on the Indonesia Stock Exchange for the 2016-2020 period.